Obesity as a Condition Determined by Food Addiction: Should Brain Endocannabinoid System Alterations Be the Cause and Its Modulation the Solution? - Marialuisa de Ceglia; Juan Decara; Silvana Gaetani; Fernando Rodríguez de Fonseca (MDPI AG, 2021)
Obesity is a complex disorder, and the number of people affected is growing every day. In recent years, research has confirmed the hypothesis that food addiction is a determining factor in obesity. Food addiction is a behavioral disorder characterized by disruptions in the reward system in response to hedonic eating. The endocannabinoid system (ECS) plays an important role in the central and peripheral control of food intake and reward-related behaviors. Moreover, both obesity and food addiction have been linked to impairments in the ECS function in various brain regions integrating peripheral metabolic signals and modulating appetite. For these reasons, targeting the ECS could be a valid pharmacological therapy for these pathologies. However, targeting the cannabinoid receptors with inverse agonists failed when used in clinical contexts as a consequence of the induction of affective disorders. In this context, new classes of drugs acting either on CB1 and/or CB2 receptors or on synthetic and degradation enzymes of endogenous cannabinoids are being studied. However, further investigation is necessary to find safe and effective treatments that can exert anti-obesity effects, normalizing reward-related behaviors without causing important adverse mood effects.